Estudo comparativo do efeito da terapia fotodinâmica e uso de antibióticos em lesões podais (Bumblefoot) em pinguins de Magalhães (Spheniscus magellanicus) - Nascimento, Cristiane Lassálvia [UNESP] (2014)
The aim of the study was to test a treatment protocol for pododermatitis class III in a group of captive Spheniscus magellanicus using photodynamic therapy (PDT) and compare it with another treated with antibiotics (ATB). All animals initially underwent surgical debridement of the lesion area and then they were randomly divided into one TFD and one ATB group, each containing 11 injuries. In the ATB group antibiotic ointment was used three times a week and systemic antibiotic and anti-inflammatory daily. In PDT group, photodynamic therapy has been applied three times a week without the use of systemic medication. Photos of the lesion area, swab for culture and sensitivity and blood for blood count and blood chemistry were collected on the first day and every 14 days for a total of 84 days. The results reaffirmed the relapsing nature of these lesions that begin from the point of support. The prevalence of bacteria over time was not uniform and there was need to carry out antibiograms at different times to select an appropriate drug. In comparison, the PDT group showed the best performance with 63.62% on an average healing time of 42 days, compared to 9.09% in an average healing time of 70 days in the ATB group. The findings of this study attest to the effectiveness of photodynamic therapy for the treatment of class III to pododermatitis Spheniscus magellanicus